Acute kidney injury: a paradigm for miRNA regulation of the cell cycle. (11th August 2014) - Khalid, Usman; Bowen, Timothy; Fraser, Donald J.; Jenkins, Robert H.
Abstract : miRNAs are small, endogenous, post-transcriptional regulators of gene expression. AKI (acute kidney injury) of various aetiologies, including trauma, sepsis and IRI (ischaemia/reperfusion injury) in the context of kidney transplantation, or drug toxicity, has a high morbidity and mortality rate and presents a significant burden to health services worldwide. AKI primarily affects the renal cortex, in particular PTCs (proximal tubular epithelial cells). Current research demonstrates causality between G2 /M cell cycle arrest of PTCs and AKI. Recent findings from our laboratory and others presented in this review implicate miRNA regulation of the cell cycle in the pathology of AKI.